Evidence for the Involvement of Lipid Rafts and Plasma Membrane Sphingolipid Hydrolases in Pseudomonas aeruginosa Infection of Cystic Fibrosis Bronchial Epithelial Cells - Schiumarini, Domitilla; Loberto, Nicoletta; Mancini, Giulia; Bassi, Rosaria; Giussani, Paola; Chiricozzi, Elena; Samarani, Maura; Munari, Silvia; Tamanini, Anna; Cabrini, Giulio; Lippi, Giuseppe; Dechecchi, Maria Cristina; et al. (Mediators of Inflammation, 2017)
Cystic fibrosis (CF) is the most common autosomal genetic recessive disease caused by mutations of gene encoding for the cystic fibrosis transmembrane conductance regulator. Patients with CF display a wide spectrum of symptoms, the most severe being chronic lung infection and inflammation, which lead to onset of cystic fibrosis lung disease. Several studies indicate that sphingolipids play a regulatory role in airway inflammation. The inhibition and downregulation of GBA2, the enzyme catabolizing glucosylceramide to ceramide, are associated with a significant reduction of IL-8 production in CF bronchial epithelial cells. Herein, we demonstrate that GBA2 plays a role in the proinflammatory state characterizing CF cells. We also report for the first time that Pseudomonas aeruginosa infection causes a recruitment of plasma membrane-associated glycosphingolipid hydrolases into lipid rafts of CuFi-1-infected cells. This reorganization of cell membrane may be responsible for activation of a signaling cascade, culminating in aberrant inflammatory response in CF bronchial epithelial cells upon bacterial infection. Taken together, the presented data further support the role of sphingolipids and their metabolic enzymes in controlling the inflammatory response in CF.